The κωμασία in Graeco-Roman Egypt: A Religious, Historiographical and Semantical Analysis - Ródenas Perea, Esperanza Macarena (ARYS. Antigüedad: Religiones y Sociedades, 2025)
Kωμασία (“procession”) and its derivatives (such as κωμαστής, “one who carries images”) are words that appear in an entirely new way in Graeco-Roman Egypt. However, even if the κωμασία is related to processions, many other Greek words referring to the processional rite are also attested in Egypt, such as πομπή, πομπαγωγία ο ἐξοδεία, which is why there is still a debate about the specific meaning of κωμασία. Some authors claim that it was a ceremony held on the adventus or arrival of an important individual, whereas others believe that it was a procession where images of the gods were carried. Finally, other scholars emphasize its oracular aspect. From all of these definitions, I will focus on the κωμασία as a procession where the images of the gods were carried. The mobility of the statues of the gods in Egypt, around which some of its most important religious festivals were articulated (such as the Opet Festival, the Beautiful Feast of the Valley, among others), make us ponder about the originality of the term κωμασία and its derivatives. To try to clarify its meaning, in this paper I will analyze several aspects of the κωμασία and its derivatives: their etymology, their contextualization within the general context of processions in Egypt, the debate on its meaning as well as their diachronic evolution, where both Egyptian tradition and the progressive adoption of Graeco-Roman traits related to the cult of the gods and the rulers may have intervened.
Keywords: komasía; komastes; procession; Graeco-Roman Egypt; imperial cult